Controls on the Transport of Meltwater From the Southern Greenland Ice Sheet in the Labrador Sea. Issue 6 (5th June 2019) - Castelao, Renato M.; Luo, Hao; Oliver, Hilde; Rennermalm, Asa K.; Tedesco, Marco; Bracco, Annalisa; Yager, Patricia L.; Mote, Thomas L.; Medeiros, Patricia M.
Abstract: Coastal waters in the Labrador Sea are influenced by the seasonal input of meltwater from the Greenland ice sheet, which is predicted to more than double by the end of the century. Mechanisms controlling the offshore export of meltwater can have a significant effect on stratification and vertical stability in the Labrador Sea, being particularly important if the meltwater is transported toward the interior of the basin where winter convection occurs. Here we use a high‐resolution ocean model to show that coastal upwelling winds play a critical role transporting the meltwater offshore to about 150 km from the coast, where increased eddy activity and mean circulation can then transport the meltwater farther offshore. While meltwater discharged from West Greenland is either transported to Baffin Bay or circumnavigates the basin flowing mostly along isobaths, meltwater from East Greenland can reach the interior of the basin where it may influence stratification and winter convection whenever winds are anomalously upwelling favorable in late summer and early fall. Plain Language Summary: Every summer, coastal waters off Greenland are influenced by the input of freshwater from ice sheet melting. Based on analyses of ocean model simulations, we show that meltwater transport in the Labrador Sea is controlled by multiple processes. Winds play an important role, transporting the freshwater to about 150 km from the coast, where the large‐scale circulation and eddies can transport the meltwater farther offshore. Most of the meltwater is transported either northward into Baffin Bay or around the basin. When winds are anomalously upwelling favorable in late summer or early fall, however, meltwater from East Greenland can be transported into the interior of the basin where it may influence vertical stratification and winter convection. Key Points: Winds play a major role transporting meltwater within 150 km from the West Greenland coast Westward veering of large‐scale circulation and eddies transport meltwater farther offshore into the Labrador Sea Meltwater from East Greenland can reach the Labrador Sea interior when winds are anomalously upwelling favorable in late summer/early fall